The rivers of milk and honey - Khan, Saniyasnain (Goodwordbooks: New Delhi, 2004)
The book narrates the splendors of paradise as described in Islamic teachings. Through simple text and vivid pictures, it depicts what lies in store for devout Muslims in the Hereafter, aiming to captivate young minds and inspire them with visions of eternal peace, abundance, and divine blessings